EXPLORING EFL STUDENTS’ PERSPECTIVES ON THE ROLE OF CHATGPT-ASSISTED AUTONOMOUS LEARNING IN ENHANCING SELF-DIRECTED LEARNING IN PALESTINIAN HIGHER EDUCATION - Al-Atrash, Aya (An-Najah National University, 2024)
This study aimed to investigate the perspectives of EFL students on the role of ChatGPT-assisted autonomous learning in enhancing self-directed learning at two Palestinian universities which are An-Najah National University and Al-Quds Open University. To achieve this aim, the researcher employed a mixed-approach research design to analyze and explain the collected data. The data were collected through the study tools which are interviews and a questionnaire from a sample of EFL students according to demographic variables such as gender, academic level, and university. An analytical descriptive approach was used by using the questionnaire as a tool for the study and was analyzed using SPSS V.23. The sample of the study consisted of (348) students chosen by stratified random method. The quantitative analysis revealed generally positive perspectives of ChatGPT’s effectiveness in fostering self-directed learning. The findings of the questionnaire showed a high response to the total degree of the main question. Moreover, there were no statistically significant differences attributed to the variables of academic level and university while there were statistically significant differences due to gender in favor of males. The qualitative data further emphasized the potential of ChatGPT to function as a supplementary tool, providing learners with ways to steer academic learning more efficiently. The study also emphasized the need for teacher guidance to ensure balanced use. Overall, ChatGPT is seen as a valuable benefit in the educational process even though its success depends on thoughtful integration with conventional teaching methods. The study ultimately recommended the necessity of raising the awareness level of perspective on the impact of ChatGPT-assisted autonomous learning in enhancing self-directed learning and profound studies about this domain.
إستكشاف وجهات نظر طلاب اللغة الإنجليزية كلغة أجنبية حول دور التعلم الذاتي بمساعدة الشات جي بي تي في تعزيز التعلم الموجه ذاتيًا في سياق التعليم العالي الفلسطيني